Analisis Sistem Pelatihan dan Pengembangan Karyawan Pada PT Kereta Api Indonesia (Persero) Divre III Palembang - Rian Hidayat; Dina Mellita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to analyze the training and development system for employees at PT Kereta Api Indonesia (Persero) Divre III Palembang, a state-owned enterprise operating in the railway transportation sector with high operational complexity and significant safety risks. The study employs a qualitative descriptive method through observation, interviews, and documentation at the Human Resources Unit of PT KAI Divre III Palembang. The findings reveal that the training and development system has been implemented comprehensively through a systematic cycle consisting of Training Need Analysis (TNA), program design, implementation using both on-the-job and off-the-job training methods, and multi-level evaluation. The utilization of the KAI Learning Center e-learning platform serves as the primary digital solution for mass knowledge distribution. The program portfolio encompasses occupational safety and health training, customer service refreshment, AKHLAK corporate culture socialization, and digitalization training. Evaluation results indicate positive impacts on employee behavior and organizational outcomes, contributing significantly to the formation of a robust talent pool that supports internal mobility policies, rotation, and promotions.